In Vivo Tracking of the Degradation of Mesoporous Silica through 89Zr Radio‐Labeled Core–Shell Nanoparticles. Issue 30 (18th June 2021) - Bindini, Elisa; Ramirez, Maria de los Angeles; Rios, Xabier; Cossío, Unai; Simó, Cristina; Gomez‐Vallejo, Vanessa; Soler‐Illia, Galo; Llop, Jordi; Moya, Sergio E.
Abstract: While mesoporous silica nanoparticles (MSNs) are extensively studied as high‐potential drug delivery platforms, the successful clinical translation of these nanocarriers strongly depends on their biodistribution, biodegradation, and elimination patterns in vivo. Here, a novel method is reported to follow the in vivo degradation of MSNs by tracking a radioactive label embedded in the silica structure. Core–shell silica nanoparticles (NPs) with a dense core and a mesoporous shell are labeled with low quantities of the positron emitter 89 Zr, either in the dense core or in the mesoporous shell. In vivo positron emission tomography imaging and ex vivo organ measurements reveal a remarkable difference in the 89 Zr biodistribution between the shell‐labeled and the core‐labeled NPs. Release of the radiotracer from shell‐labeled NPs is used as a probe of the extent of silica dissolution, and a prompt release of the radioisotope is observed, with partial excretion already in the first 2 h post injection, and a slower accumulation in bones over time. On the other hand, when 89 Zr is embedded in the nanoparticle core, the biodistribution remains largely unchanged during the first 6 h. These findings indicate that MSNs have fast, hour‐scale, degradation kinetics in vivo. Abstract : Degradation of mesoporous silica nanoparticles is investigated in vivo, using radio‐labeled PEGylated core–shell silica nanoparticles (NPs) with a dense core and a mesoporous shell. While core‐labeled NPs provide information on NP biodistribution, the fate of degradation products of the mesoporous silica is traced from the shell‐labeled NPs silica. A fast, hour‐scale degradation kinetics is observed.